Odmienność, awangarda i gry wideo: recenzja książek Video Games Have Always Been Queer oraz The Queer Games Avant-Garde: How LGBTQ Game Makers Are Reimagining the Medium of Video Games - Piotr Krzywdziński (Wydawnictwo Uniwersytetu Gdańskiego, 2020)
Recenzja książek Video Games Have Always Been Queer oraz The Queer Games Avant-Garde: How LGBTQ Game Makers Are Reimagining the Medium of Video Games